Development of learning media for square topics using scratch platform for grade VII - Al jabar, Sheila Zalzabilla; Supriatna, Tatang (CV. Pustaka Literasi Ilmiah, 2023)
This research aims to develop teaching materials for quadrilateral topics assisted by Scratch with valid, practical, and effective quality based on the stages of geometry skills using the Research and Development (R&D) method. The subject of this study involved a limited trial conducted at Sumur Bandung Junior High School in Cililin, with 10 students from 7th grade. A broader trial was conducted at Sumur Bandung Junior High School in Cililin, with 45 students from 7th grade. The final product was tested at Sumur Bandung Junior High School in Cililin, consisting of two classes: an experimental class (VII-A) and a control class (VII-B), each comprising 22 and 23 students, respectively. Data collection techniques employed were observation, interviews, and documentation. The data analysis involved descriptive statistics and inferential statistics. The instruments used in this study were reasoning ability tests based on mathematical reasoning indicators and interview questionnaires. The research findings indicated that the use of Scratch-assisted teaching materials had a positive impact, enhancing students' mathematical reasoning ability to an excellent category. Students who learned with the Scratch-assisted materials demonstrated better mathematical reasoning ability compared to those who received conventional instruction. Therefore, the Scratch-assisted teaching materials were considered valid and effective for instructional purposes.